Keanekaragaman Morfologi Durian Lokal (Durio zibethinus Murr) di Aceh Tamiang, Indonesia - Chelsea Ruth Maranatha; Nurul Koimah; Juni Artika (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samudra, 2020)
Aceh Tamiang is one of durian fruit production with ± 603 per ton production per year and also has a high biodiversity of fruits and vegetables. Durian diversity is a potential that can be seeded. The purpose of this study was to determine the diversity of durian varieties found in Tualang village, Aceh Tamiang based on morphological characteristics. This research is descriptive in nature which describes variable conditions. This research was conducted in the village of Tualang Niat Kampung Selamat District Tenggulun, Aceh Tamiang. The collected data is then calculated using the equation formula of the STO pair association (Operational Taxonomy). The results of this study indicate that the diversity of local durian Tualang Village there are 7 local varieties of durian fruit, including copper durian, montong durian, heart durian, milk durian, weasel king durian. The highest similarity index is 50 and the lowest similarity is 21.42. The difference is influenced by environmental factors that cause morphological changes in the durian.